Short term effect of thiamethoxam on glutamate dehydrogenase (GDH) activity in Snake head, Ophiocephalus punctatus - Chilke, Arun M. (Journal of Research in Biology, 2011)
An organochloride, thiamothoxam is used commercially for controlling the agricultural pest. In the present study it was observed that at sub-lethal concentration (29.483 ppm) the GDH activity in the liver, kidney, gill and muscle of Ophiocephalus punctatus increased non-significantly from 24hrs to 96hrs of exposure. The maximum activity in all these organs was at 96 hrs. It has been concluded that thiamethoxam at sub-lethal concentration may alter the glutamate metabolism in all the tissues by enhancing the GDH activity in short duration of exposure